1998
DOI: 10.1038/bjc.1998.58
|View full text |Cite
|
Sign up to set email alerts
|

CPT-11 sensitivity in relation to the expression of P170-glycoprotein and multidrug resistance-associated protein

Abstract: Summary The relevance of P170-glycoprotein (P-gp) and multidrug resistance-associated protein (MRP) for the sensitivity to CPT-11 was investigated in human malignant cell lines as well as in human tumour xenografts. In vitro, the P-gp-positive sublines BRO/mdrl.1 (transfected with MDR1) and 2780AD were slightly cross-resistant against carboxylesterase-activated CPT-11. Cross-resistance against SN-38 was present in 2780AD cells, but not in BRO/mdrl.1 cells. The P-gp modulators BIBW22BS, verapamil and dexniguldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…These differences were not due to different levels of top1, as evaluated by a semiquantitative method (Murphy et al, 1990), as already published (Goldwasser et al, 1995;van Ark-Otte et al, 1998). Jansen et al (1998) proposes a role for P-glycoprotein (encoded by mdr1 gene) in lack of efficacy of numerous compounds, including CPT-11. Our study did not support such a role as no correlation was found between P-glycoprotein encoding gene expression (MDR1) and CPT-11 responses and, furthermore, a diversity of mdr1 gene expression (a range of 80-fold) in our series of CRCs was shown.…”
Section: Discussionmentioning
confidence: 50%
“…These differences were not due to different levels of top1, as evaluated by a semiquantitative method (Murphy et al, 1990), as already published (Goldwasser et al, 1995;van Ark-Otte et al, 1998). Jansen et al (1998) proposes a role for P-glycoprotein (encoded by mdr1 gene) in lack of efficacy of numerous compounds, including CPT-11. Our study did not support such a role as no correlation was found between P-glycoprotein encoding gene expression (MDR1) and CPT-11 responses and, furthermore, a diversity of mdr1 gene expression (a range of 80-fold) in our series of CRCs was shown.…”
Section: Discussionmentioning
confidence: 50%
“…In selected cell lines expressing P-glycoprotein, this transporter appeared to influence the sensitivity to CPT-11 and SN-38 in vitro, but this had little influence on the activity of the drugs in xenografts (Jansen et al, 1998). Moreover, MRP expression did not appear to affect the activity of CPT-11 or SN-38.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of ABC transporters is associated with resistance to SN-38 in several malignant cell lines (36). In addition, the ABCC1 pump has higher affinity to SN-38 than any other Figure 4.…”
Section: Discussionmentioning
confidence: 99%